1979
DOI: 10.1002/j.1879-3479.1979.tb00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Postcoital Contraception

Abstract: Yuzpe AA (Dept of Obstetrics and Gynecology, University of Western Ontario, London, Ontario, Canada). Postcoital contraception. Int J Gynaecol Obstet 16: 497–501, 1979 The evolution of postcoital contraception has led to the development of emergency measures to be used following a single unprotected act of intercourse and to ongoing methods, such as the administration of a contraceptive steroid agent following every coital exposure. In emergency situations, the most commonly employed hormonal steroids are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The combined regimen was shown by Ling et al to produce asynchronous development of the glandular and stromal elements of the endometrium, with the glands lagging behind the stroma [56]; this has been confirmed by others [20]. At a cellular level, following combined therapy, a significant reduction in endometrial oestrogen and progesterone receptors is demonstrated [60,61].…”
Section: Mechanisms Involving the Uterusmentioning
confidence: 77%
See 1 more Smart Citation
“…The combined regimen was shown by Ling et al to produce asynchronous development of the glandular and stromal elements of the endometrium, with the glands lagging behind the stroma [56]; this has been confirmed by others [20]. At a cellular level, following combined therapy, a significant reduction in endometrial oestrogen and progesterone receptors is demonstrated [60,61].…”
Section: Mechanisms Involving the Uterusmentioning
confidence: 77%
“…A combination of ethinyloestradiol and norgestrel has been in use since the early seventies [20]. A combination of ethinyloestradiol and norgestrel has been in use since the early seventies [20].…”
Section: Oestrogen-progestogen Combinationmentioning
confidence: 99%
“…First described by Yuzpe and Lancee 32 , this combination therapy is often referred to as the Yuzpe regimen. The oestrogen–progestin regimen consists of two doses of a combination of 100 μg of ethinyl estradiol and 0.5 mg of levonorgestrel each, the first dose taken within 72 hours of intercourse and the second dose 12 hours later 33–37 . This is the most commonly used emergency contraceptive.…”
Section: Methods Of Emergency Contraceptionmentioning
confidence: 99%
“…Copper IUDs for emergency contraception are more effective in preventing unwanted pregnancy (pregnancy rate <0.1%) than postcoital pills, such as levonorgestrel emergency contraceptive pills, since efficacy decreases more rapidly with time 51 . When efficacy is a priority, the IUD is the emergency contraceptive of choice 52 …”
Section: Emergency Contraceptionmentioning
confidence: 99%